(untitled) (BIRDEM Medical Journal, 2020)
Background: Diabetes mellitus (DM) is the leading cause of chronic kidney disease through-out the world andhalf of the type 2 DM (T2DM) patients remain undiagnosed. During diagnosis, one-third to half of the T2DMpatients may have different macro- and micro-vascular complications including diabetic nephropathy. This studyaimed to evaluate selected risk factors for diabetic nephropathy among newly detected T2DM subjects. Methods: A case-control study was done at out-patient department of BIRDEM General Hospital, Dhaka,Bangladesh from October 2016 to June 2017. Newly detected (<3 months) adult (³18 years) T2DM patientswere included in this study. Patients with diagnosed kidney diseases, features of glomerulonephritis, systemicdiseases like systemic lupus erythematosus and vasculitis, history of recent fever and exercise, urinary tractinfection and pregnancy were excluded. Patients with urine albumin-creatinine ratio (UACR) ³30 mg/g in atleast two (of three, if done) samples were cases and those with UACR <30 mg/g were controls. Results: Total patients were 100, including 35 cases [microalbuminuria (UACR 30-299 mg/g) = 33 and overtproteinuria (UACR ³300 mg/g) = 2] and 65 controls. Mean age was 46.6±12.3 years and there was femalepredominance (male:female ratio was 1:2). One-fourth patients were smokers, half were hypertensive andtwo-fifths had dyslipidaemia. Three-fourths of the study participants had positive family history of DM andtwo-fifths had family history of diabetic nephropathy. Mean body mass index (BMI) was 26.26±2.97 kg/m2.Mean fasting blood glucose (mmol/L), 2-h post glucose value (mmol/L) and mean glycatedhaemoglobin(HbA1c) (%) were 9.2±2.9, 14.5±4.1 and 7.9±1.3 respectively. Eighty percent of the patients were asymptomaticregarding DM. Besides nephropathy, other chronic complications of DM were diabetic retinopathy (17%),neuropathy (11%), coronary artery disease (11%) and cerebrovascular disease (4%). Regarding risk factorsfor diabetic nephropathy, family history of DM (OR 1.62, p 0.0001) and diabetic nephropathy (OR 25.13,p 0.003), presence of hypertension (OR 4.93, p 0.001) and coexisting diabetic retinopathy (OR 14.18, p 0.046)were significant. On multivariate logistic regression, family history of DM (OR 1.77, p 0.001) and diabeticnephropathy (OR 24.31, p 0.001), higher BMI (>25 kg/m2) (OR 2.11, p 0.013), hypertension (OR 4.31,p 0.003) and diabetic retinopathy (OR 14.09, p 0.021) were significant. Conclusions: One-third of the newly detected T2DM subjects had diabetic nephropathy in this study. Familyhistory of DM and nephropathy, higher BMI, presence of hypertension and diabetic retinopathy were significantrisk factors for diabetic nephropathy. Birdem Med J 2020; 10(2): 88-91